Hybrid passive micromixer using combined traditional microfabrication and 3D printing for gold nanoparticle synthesis - Yasser Aldaghestani; Andreas Schiffer; Anas Alazzam (PLoS ONE, 2026)
This study introduces a novel hybrid passive micromixer that seamlessly integrates conventional microfabrication techniques with cost-effective 3D printing to facilitate the controlled synthesis of nanoparticles with high precision in size and morphology. The micromixer design combines a Y-junction microchannel fabricated using soft lithography with an embedded 3D-printed helical structure to enhance mixing efficiency. Notably, the helical structure was fabricated using a commercially available, cost-effective Digital Light Processing (DLP) 3D printer, demonstrating that high-performance microfluidic devices can be manufactured without reliance on expensive, specialized equipment. Numerical simulations were conducted to analyze the micromixer parametrically and to compare its performance to various micromixer designs reported in the literature. The results reveal the superiority of the mixing capabilities of the proposed mixer under laminar flow conditions. Experimental validation using dyed fluids and image analysis techniques confirmed the enhanced mixing performance of the hybrid micromixer, reaching a mixing efficiency of 92% at a Reynolds number of 1, with results closely matching the numerical predictions. The device was then used in the synthesis of gold nanoparticles, employing L-ascorbic acid as the reducing agent. Characterization of the synthesized nanoparticles via UV-Vis spectroscopy and scanning electron microscopy (SEM) demonstrated precise control over particle size and distribution, with gold nanoparticles ranging from 14 to 25 nm at a total flow rate of 5000 µL/min. This hybrid micromixer approach offers a scalable, efficient, and accessible platform for nanomaterial synthesis, with potential applications in fields such as drug delivery, biosensing, and catalysis.